Protein and Signaling Pathway Responses to rhIL-6 Intervention Before Lobaplatin Treatment in Osteosarcoma Cells - Wang, Huan; Li, Bin; Yan, Kang; Wu, Yonghong; Wen, Yanhua; Liu, Yunyan; Fan, Pei; Ma, Qiong (Frontiers in Oncology, 2021)
Lobaplatin is a third-generation platinum-based antineoplastic agent and is widely used for osteosarcoma treatment before and after tumor removal. However, treatment failure often results from lobaplatin drug resistance. In our study, we found that SaOS-2 and SOSP-9607 osteosarcoma cells became less sensitive to lobaplatin after treatment with exogenous interleukin (IL)-6. Quantitative proteomic analysis was performed to elucidate the underlying mechanism in SaOS-2 osteosarcoma cells. Cells were divided into a control group (CG), a lobaplatin treatment group (LG) and a recombinant human IL-6 (rhIL-6) and lobaplatin group (rhILG). We performed three biological replicates in each group to compare the differential protein expression between groups using tandem mass tag (TMT) labeling technology based on liquid chromatography-tandem mass spectrometry (LC-MS/MS). A total of 1,313 proteins with significantly differential expression were identified and quantified. The general characterizations of significantly enriched proteins were identified by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, and protein-protein interaction (PPI) analysis was conducted using IntAct and STRING. In total, 31 proteins were further verified by parallel reaction monitoring (PRM), in which ras GTPase-activating protein-binding protein 1 (G3BP1), fragile X mental retardation syndrome-related protein 1 (hFXR1p) and far upstream element-binding protein 1 (FUBP1) were significantly differentially expressed. Immunohistochemistry results showed that these three proteins are highly expressed in specimens of platinum-resistant osteosarcoma patients, while the proteins are negatively or weakly expressed in specimens of platinum-sensitive osteosarcoma patients. The results of immunofluorescence staining were in accordance with those of immunohistochemistry staining. This is the first proteomic study on rhIL-6 intervention before lobaplatin treatment in osteosarcoma cells.